2015
DOI: 10.1007/s12298-015-0282-6
|View full text |Cite
|
Sign up to set email alerts
|

High frequency organogenesis in hypocotyl, cotyledon, leaf and petiole explants of broccoli (Brassica oleracea L. var. italica), an important vegetable crop

Abstract: Broccoli (Brassica oleracea L. var. italica) is an important, nutritionally rich vegetable crop, but severely affected by environmental stresses, pests and diseases which cause massive yield and quality losses. Genetic manipulation is becoming an important method for broccoli improvement. In the present study, a reproducible and highly efficient protocol for obtaining organogenesis from hypocotyl, cotyledon, leaf and petiole explants of broccoli (Brassica oleracea L. var. italica cv. Solan green head) has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Zhang and Bhalla [34] reported huge variations (0-96.7%) in seven Australian cultivars of Brassica napus. Similar genotype-dependent variations among different Brassica species have been reported in several studies [23,33,[35][36][37][38][39][40]43,[45][46][47]49].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Zhang and Bhalla [34] reported huge variations (0-96.7%) in seven Australian cultivars of Brassica napus. Similar genotype-dependent variations among different Brassica species have been reported in several studies [23,33,[35][36][37][38][39][40]43,[45][46][47]49].…”
Section: Discussionsupporting
confidence: 84%
“…Regeneration in Brassica has been reported from several tissues and organs including leaves, stem sections, petioles, roots, hypocotyls, cotyledons, immature zygotic embryos, protoplasts and cell suspension cultures [16,27,[33][34][35][36][37][38][39][40][41]. Out of these, cotyledons, hypocotyls and roots have been frequently used for genetic transformation [2,16,19,37,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro plant regeneration studies in broccoli using several types of explants have been reported by various workers, viz., peduncle (Christey and Earle 1991), anther (Chang et al 1996), hypocotyl (Zhong and Li 1993;Puddephat et al 2001;Kim and Botella 2002;Ravanfar et al 2009;Huang et al 2011), leaf tissue (Robertson and Earle 1986;Cao and Earle 2003;Kumar and Srivastava 2015) and cotyledon (Qin et al 2006;Ravanfar et al 2011). Thidiazuron, (N 0 -phenyl-N 0 -1,2,3-thidiazol-5-ylurea, TDZ) is a phenyl urea that has gained importance as a potent plant growth regulator (PGR) for in vitro regeneration systems of various crops (Murthy et al 1995;Guo et al 2005;Ravanfar et al 2014).…”
Section: Introductionmentioning
confidence: 99%